1991
DOI: 10.1203/00006450-199104000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Maturation of Ventilatory Responses to 1-Minute Exercise

Abstract: ABSTRACT. To test the hypothesis that ventilatory responses to exercise mature during growth in healthy children, we examined C 0 2 production (VCO~) and minute ventilation (VE) before, during, and for 10 min after 1-min bursts of cycle ergometry exercise. Ten children (range: 7-11 y old) and 13 adults (26-42 y old) exercised at work rates corresponding to 50 and 80% of the anaerobic or lactate threshold, 50% of the difference between anaerobic threshold and maximum 0 2 consumption, 100% of maximum O2 consumpt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(15 citation statements)
references
References 18 publications
(20 reference statements)
2
13
0
Order By: Relevance
“…While only speculative, this assertion is supported by incomplete maturation of ventilatory control mechanisms, such as the peripheral chemoreceptors in children (Springer et al 1988). Others have found evidence for a lower arterial CO 2 partial pressure set-point, (Brady et al 1964;Brady and Ceruti, 1966) causing higher levels of ventilation for a given CO 2 (Cooper et al 1987;Armon et al 1991b;Pianosi and Wolstein 1996;Nagano et al 1998), increased ventilatory sensitivity to CO 2 and greater respiratory responsiveness (Gratas-Delamarche et al 1993) in children compared to adults.…”
Section: Noise Magnitudementioning
confidence: 95%
“…While only speculative, this assertion is supported by incomplete maturation of ventilatory control mechanisms, such as the peripheral chemoreceptors in children (Springer et al 1988). Others have found evidence for a lower arterial CO 2 partial pressure set-point, (Brady et al 1964;Brady and Ceruti, 1966) causing higher levels of ventilation for a given CO 2 (Cooper et al 1987;Armon et al 1991b;Pianosi and Wolstein 1996;Nagano et al 1998), increased ventilatory sensitivity to CO 2 and greater respiratory responsiveness (Gratas-Delamarche et al 1993) in children compared to adults.…”
Section: Noise Magnitudementioning
confidence: 95%
“…However, it is.becoming clear that remarkable differences between children and adults do exist. For example, after I min of exercise on a'constant-power cycle ergometer in the high-intensity range, we found that the recovery time for Veo z was substantially shorter in children (recovery time constant of about 45 s) compared with adults (recovery time constant about 85 s) (22). Similar differences were observed for VE and HR (23).…”
Section: A Proposalmentioning
confidence: 59%
“…Ohuchi et al 31 demonstrated that the magnitude and change in end-tidal to arterial carbon dioxide tension difference P(ET-a)DCO 2 during graded exercise were smaller, with children showing lower values than adults in both at anaerobic threshold and peak of exercise. We postulate that this finding may be explained by a lower ventilatory efficiency 4,13,[25][26][27] and a lower glycolytic capacity during exercise in children than adults [1][2][3][6][7][8][9] .…”
Section: Figure 1 -A) Rr -Respiratory Rate; B) Ve -Pulmonary Ventilatmentioning
confidence: 82%
“…These findings emphasized that the ventilatory pattern in pediatric population is dependent on maturity 2,25-27 . In the same context, Armon et al 27 observed in children higher pulmonary ventilation for a given VCO 2 as compared to adults. What is the explanation for these findings?…”
Section: Figure 1 -A) Rr -Respiratory Rate; B) Ve -Pulmonary Ventilatmentioning
confidence: 88%